Hubungan Kualitas Pelayanan Persalinan Dengan Kepuasan Ibu Bersalin Di Puskesmas Padang Tahun 2022 - Ambarsari, Retno Dwi; Endah Sary, Yessy Nur; Azizah, Fifin Maulidatul (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Maternal and child health is still a major problem in Indonesia and a priority in health development. Maternal and infant mortality itself is influenced by various factors, one of which is the quality of existing health services. This study aims to analyze the relationship between the quality of maternity services with maternal satisfaction.This research is a correlational study using a cross sectional approach. Data were taken using a questionnaire to mothers who gave birth at the Padang Health Center in August 2022. Using a sequential sampling technique based on inclusion and exclusion criteria, a total of 31 respondents made up the study's sample. Using SPSS 2.0, I examined and tested the chi square. It was discovered that there is no relationship between the quality of maternity services based on the tangible dimension (p=0.519) and maternal satisfaction, no relationship between the quality of maternity services based on the reliability dimension (p=0.527), no relationship between the quality of maternity services based on the responsiveness dimension (p=0.791), and there is a relationship between quality of maternity services and quality of life (p=0.791).It is hoped that the Padang Health Center will be able to improve midwifery care, especially in providing quality of maternity service based on tangible, reliability, responsiveness, assurance and empathy dimensions as an effort to increase patient satisfaction.